Budaya “Ewuh Pakewuh”, Kecurangan, dan Sistem Whistleblowing: Perspektif Psikologi dan Budaya Berdasarkan Teori Perilaku Terencana - Sampe Tondok, Marselius; Widayati, Irma (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The results of the fraud survey in Indonesia in 2019 show that out of 239 cases of fraud found, 167 cases (69.9%) were related to corruption. Three conditions trigger fraud: pressure, opportunity, and rationalization. Fraud has a harmful impact, whether financial or non-financial, and therefore prevention efforts are needed such as implementating a whistleblowing system. Cultural factors significantly impact the effectiveness of such systems. This study explores the